Understanding toxic elements in agricultural products: integrating insights from ionomics and arsenic speciation - Jones, Rachel Rose, author; Prenni, Jessica, advisor; Chitwood-Brown, Jessica, committee member; Davis, Jessica, committee member; Rhodes, Davina, committee member (Colorado State University. Libraries, 2024)
We humans are very unlikely to move through the world without encountering toxic elements. Throughout our history, we have viewed toxic elements through a variety of lenses: as medicines, poisons, plumbing material, pesticides, environmental threats. They are present in air, soil, water, and – as a result – food. Their geographic distribution is influenced by both natural geologic processes and our own actions, and the burden of exposure does not necessarily fall equitably across communities. Different toxic elements have different physiological effects, threshold concentrations of concern, and distributions in the food supply. Even a single toxic element can take on various chemical forms with varying toxicities. These elements continue to cause human suffering as they make their way into our diets, and we continue to learn about them. However, the large degree of chemical variation associated not only with toxic elements themselves, but also the food matrices they exist within, demand ongoing development of robust analytical methods. This dissertation assesses current availability and operationalization of data on toxic metals in the food supply and discusses a study of many different elements – including multiple toxic elements – in diverse foods. This study illustrates the importance of both understanding the large variation in toxic metal concentrations that can exist between different foods, and the co- occurrence of toxic and nutritive elements in foods. The second half of the dissertation focuses more specifically on arsenic, which is acutely toxic in some chemical forms, much less worrying in others, and of uncertain concern in others still. Understanding the distribution of these chemical forms in a high-arsenic matrix is critical for understanding the potential risk posed by the product. Analytical techniques capable of providing this data are known as speciation methods. After describing development of an arsenic speciation method in hemp, the dissertation concludes with a study applying the method to a panel of foods that may be high in total arsenic.